Analisis Pembelajaran Daring Terhadap Motivasi Belajar Siswa Kelas V SD Inpres Borong Jambu II Kota Makassar - Rani Patty; Nurhadifah Amaliyah; Cayati; Muhammad Khaedar (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
This study aims to determine the analysis of online learning on students' learning motivation compared to face-to-face learning of fifth grade students at SD Inpres Borong Jambu II Makassar City. data collection instruments in the form of observation, interviews, and documentation. The research method used in this study is a descriptive qualitative research method using data collection techniques, namely interview techniques. The author uses interview techniques by collecting information from 1 principal, 1 homeroom teacher for class V, and 3 students from the class he/she teaches. Based on the joint interviews of 1 school principal, 1 homeroom teacher for class V, and 3 of these students, it was found that these students experienced a decrease in their learning motivation during online learning compared to face-to-face learning motivation. The cause of this decrease in student learning motivation is that students receive a lot of comprehensive and direct assistance from parents who accompany students when doing online learning. However, it was also found that the impact of such online assistance would have a negative impact on future student development. The negative impact on student development is that students don't care or seem to underestimate each of their assignments. In addition, students will also depend more on the help of others so that they become less independent individuals. In the end, the condition of students who are less independent will also often make it difficult for parents to direct students to complete each task and responsibility in their school.